Bandidos e elites citadinas na África romana : um estudo sobre a formação de estigmas com base nas Metamorphoses de Apuleio de Madaura (século II) - Lima Neto, Belchior Monteiro (2011)
This dissertation examines a very present issue: the construction of identities. Our aim is to demonstrate how questions about the identities could be thought, questioned and interrogated in the Ancient World. So, we had as source the Metamorphoses of Apuleius, author of North African mid-second century. Through this Latin novel, this fiction, we seek to understand the representations that our author attributed to different social groups. In it, we found a dichotomous process in which bandits and elites townspeople, city and countryside, were put into binary oppositions and with several different valuations. To latrones and to the hinterland where they lived were related representations denoting savagery, hostility, aggressiveness and violence, important elements in the formation of a stigmatized identity in relation to bands of robbers. To members of municipal aristocracies and to North African cities where they lived were associated signs of distinction, wealth and high culture, which would be linked to roman paideia and humanitas. It is the size of this finding in our primary documentation we could infer that the central hypothesis of this work, that the stigma of the bandits were related, through the otherness, to a process of constituting the identity of the elites townspeople north african and reflected a reality of conflict and dichotomy between the roman civitates and the vast hinterland north african in the context of the second century.